Current status of skilled clinical engineer in developing countries - Md. Anwar, Hossain; M. A., Rashid; Md. Rafiqul, Islam; Mohiuddin, Ahmad (2015)
With the rapid development of medical technology for the last 30 years the clinical engineering practice was introduced in developed countries. But in developing countries, such as Nepal, Bangladesh, Malaysia and so many, this profession is totally a new concept. The medical equipment in the most developed countries is maintained by the clinical engineers whereas in developing countries like Nepal, Bangladesh and Malaysia are maintained by unskilled professional. A series of publication indicate that a lot of sophisticated modernized costly medical equipment could not be kept in a safe and optimum functional condition through the traditional short-trained electrical/mechanical engineers. This paper explores the importance of clinical engineering practice in developing countries of south Asia and its benefits for healthcare service. In this paper, authors propose a novel method for clinical engineering practice for the developing countries to sustain safe use and economical maintenance. This method will not only increase the clinical engineering practice but also help to get optimum feedback through clinical engineers. It should be noticed here that the different developed countries are producing and introducing clinical engineers in health care technology management in different ways, but those methods seem to not be suitable for the developing countries like Bangladesh based on the country contexts. The proposed method will change the health services top level managers and users of the medical equipment. It is ascertained that the performance of the health care technology will be improved by introducing this professional in the hospitals. This study will be much worthy to produce and introduce clinical engineers in order to improve the existing performance of healthcare services in developing countries like Bangladesh significantly.